A study on the Chinese Taipei top-tier badminton players` sponsorship - Tseng, Y.; Cheng, S. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction Sports sponsorship has become a vital strategy in corporate marketing. While sponsorships involving sports events, organizational entities, and venue naming rights are common, athlete endorsements often yield superior results. However, conflicts between athletes and sponsoring brands frequently arise, which few of the previous researches in Chinese Taipei have been discussed from the perspective of athlete endorsements. This paper supplements this perspective, aiming to understand the overview of corporate sponsorship of badminton in Chinese Taipei, the current status of athletes receiving corporate sponsorship and their understanding of sponsorship. The goal is to foster mutually beneficial relationships between corporations and athletes. Method This study employs a semi-structured interview method. Data collection is based on the theoretical framework formed around the four major benefits of sports sponsorship proposed by Howard and Crompton (1995), the basic standards of endorsers proposed by Micik and Shanklin (1994), and the "FRED (representing Familiarity, Relevance, Esteem, and Differentiation)" principle of ideal endorser selection factors proposed by Cheng (2001). Ten top badminton players from Chinese Taipei, who have participated in the Olympic event, are selected for interviews. Data analysis involves coding the interview text according to the interview outline, followed by classification, reorganization, and comparison with existing literature. Results (1) Enterprises and corporate teams have established performance-oriented signing mechanisms, tending to provide excellent sponsorship resources for top athletes. They primarily assess athletes based on the professionalism of their sports projects, competition results, social image, and potential when selecting athletes as brand endorsers or training targets. (2) Athletes have a certain understanding of the traits of endorsers and how to maintain good relationships with sponsors, but their understanding of sponsorship concepts and long-term partnerships with sponsors is limited. (3) Sponsorship conflicts often occur when athletes receive sponsorships from similar enterprises, which are often caused by competition between enterprises. Discussion To promote better cooperation and reduce sponsorship conflicts, athletes should understand the basic concepts of sports sponsorship and the traits required of endorsers. Management departments should address issues such as lack of resources for athletes and encourage enterprises to invest in sports sponsorship to improve athletes competitive levels and promote sponsoring enterprises.